Macrophages in Renal Injury, Repair, Fibrosis Following Acute Kidney Injury and Targeted Therapy - Chen, Hui; Liu, Na; Zhuang, Shougang (Frontiers in Immunology, 2022)
Acute kidney injury (AKI) is a renal disease with a high incidence and mortality. Currently, there are no targeted therapeutics for preventing and treating AKI. Macrophages, important players in mammalian immune response, are involved in the multiple pathological processes of AKI. They are dynamically activated and exhibit a diverse spectrum of functional phenotypes in the kidney after AKI. Targeting the mechanisms of macrophage activation significantly improves the outcomes of AKI in preclinical studies. In this review, we summarize the role of macrophages and the underlying mechanisms of macrophage activation during kidney injury, repair, regeneration, and fibrosis and provide strategies for macrophage-targeted therapies.